Treatment of Kynol fiber materials – Part 1: dyeing processes - Juan Wang; Boris Mahltig (Communications in Development and Assembling of Textile Products)
Kynol fibers are excellent flame-retardant materials used for manifold applications. These fibers exhibit originally an orange coloration. Up to now, dyeing processes for Kynol fibers are less reported, and the functionalization of these fibers by finishing processes is less investigated. With this background, the main aim of this paper is the evaluation of different dyeing processes for Kynol fiber materials – a woven fabric and a non-woven material. The following types of dyestuff are evaluated – direct dyes, vat dyes, disperse dyes and color pigments. The reached color quality is determined by CIE L*a*b* indices. Dry and wet rubbing fastness is measured. Finally, best results are gained by application of disperse dyes. The gained results could be used in future also to develop other functional treatments of Kynol fibers in different fields for, e.g., light protection, UV-stability, water repellency or antistatic properties.